Yield and nitrogen use efficiency as influenced by rates of nitrogen fertilizers of some Tunisian durum wheat cultivars - Ayadi S.; Karmous C.; Trifa Y.; Hammami Z.; Rezgui S. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
Nitrogen use efficiency of durum wheat grain (Triticum turgidum ssp. durum), as valuable indicator for rational N fertilization supply, was investigated in a field experiment in the subhumid area of Tunisia with four durum wheat genotypes: two improved genotypes and two landraces, grown under three mineral N fertilization treatments (0,75 and 150 kg N ha-1) during two cropping seasons (2008/09, 2009/10). Total N content in grain, yield, N uptake by grain, and soil N (N-NH4, N-NO3) status were examined to indicate relations between N trial treatments and growing years. Analysis of variance indicated that significant interaction was noted for nitrogen x years and genotypes. Over total investigated period, above-mentioned factors significantly differ per nitrogen levels and years. The highest total N content in durum wheat grain was recorded in N150 treatment during 2009/10, but the highest yield was reached in 2008/09 growing season under 150 kg N ha-1. Drought and elevated temperatures prevailing during 2009/10 cropping season were associated with lower yielding ability of most genotypes along with higher NUE per fertilization treatment, compared to 2008/09. NUE values varied from 7.85% in 2008/09 up to 24% in 2009/10 for the 150 kg N ha-1 treatment. During investigated growing years NUE was increased with increasing nitrogen fertilization levels.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)